IMPLEMENTATION OF WOMEN EMPOWERMENT POLICIES BY THE GOVERNMENT IN EFFORTS TO HANDLE VICTIMS OF SEXUAL VIOLENCE IN THE WORK ENVIRONMENT - Oki Safitri; Sherly Fitria; Intan Normahfudi; Muhammad Naufal Daffa; Riyan Sisiawan (Ecopreneur.12, 2023)
This study aims to find out how the implementation of women's empowerment policies in efforts to prevent sexual violence in the work environment. This type of research is qualitative research using the SLR (Literature Review System) method. SLR is a literature review method that is carried out by collecting, identifying, concluding, critically evaluating research results on certain topics. The results of the study indicate that there are efforts to empower women through complaints handling, medical, psychological-spiritual services, law enforcement and assistance, as well as return and social reintegration. Thus, it can be interpreted that the policy of protecting women is one of the government's policies to facilitate, assist, and support victims of gender-based violence to obtain justice in demanding their rights. So that with this policy it is hoped that women will be able to develop their potential, so that women can be independent and participate in efforts to prevent sexual violence in the workplace.